2018
DOI: 10.3390/agronomy8060094
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Wheat Grain Yield Drivers in a Mapping Population in the UK

Abstract: Improving crop yields arises as a solution to ensure food security in the future scenarios of a growing world population, changes in food consumption patterns, climate change, and limitations on resources allocated to agriculture. Defining traits that can be reliable cornerstones to yield improvement and understanding of their interaction and influence on yield formation is an important part of ensuring the success of breeding programs for high yields. Traits that can drive yield increases, such as light inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
(30 reference statements)
3
19
0
Order By: Relevance
“…This could be explained by our assumptions about optimum agronomic management practices for effectively meeting N demand and achieving effective biological controls for any weed, disease and pest infestations, factors that generally reduce farmers’ as well as the national yields. However, mean current wheat yields of the present study are close to good year wheat yields (8–14 t ha −1 ) as reported by various studies across the UK and NZ 42,59,61,63,64 . Management optimal wheat yield potentials had been estimated and reported in the range of 7–13 t ha −1 in the north-western Europe including the UK mainly due to favourable climatic conditions and adapted local cultivars 15,19 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This could be explained by our assumptions about optimum agronomic management practices for effectively meeting N demand and achieving effective biological controls for any weed, disease and pest infestations, factors that generally reduce farmers’ as well as the national yields. However, mean current wheat yields of the present study are close to good year wheat yields (8–14 t ha −1 ) as reported by various studies across the UK and NZ 42,59,61,63,64 . Management optimal wheat yield potentials had been estimated and reported in the range of 7–13 t ha −1 in the north-western Europe including the UK mainly due to favourable climatic conditions and adapted local cultivars 15,19 .…”
Section: Resultssupporting
confidence: 87%
“…Higher mean annual precipitation in NZ (40%) than the UK could also be other reason of high yield potential in NZ, particularly under water limited condition for I W . The greater yield potential and field grain yields of winter wheat in NZ than in the UK have been reported by various studies 17,42,5961 .…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, accessions undergoing NDVI or δ 13 C assessment should have similar phenology, otherwise the phenotypic performance of these traits may be biased. Our results concur with a recent report on wheat [69] that advocates the phenotyping of photosynthetic traits at multiple scales (leaf to canopy) and multiple development stages (vegetative, and pre-and post-anthesis). Additionally, our study highlights the confounding effect of phenology when phenotyping other agronomic traits, a well-known issue when interpreting the effects of QTL for drought-related proxies of biomass and yield productivity [47,70].…”
Section: Concluding Remarks On How and When To Use Phenotyping Traitssupporting
confidence: 92%
“…The increases in grain yield of low chemical fertilizers substitute rates treatments might be due to the positive effects of organic manure and biofertilizers on wheat plants. As previously reported, organic manure amendment had the advantages of slowly releasing nutrients and preventing losses due to leaching [39,40] while biofertilizers could produce vitamins and substances that were beneficial to root development [32,41], which can promote wheat plants to absorb more nutrients.…”
Section: Discussionmentioning
confidence: 98%